STUDY ON CLOUD COMPUTING FOR EFFICIENT RESOURCE ALLOCATION AND SCHEDULING APPROACHES - KUMAR, ATHMAKURI NAVEEN (The journal of contemporary issues in business and government, 2022)
The term "cloud storage" refers to a variety of online services that enable users to store and share digital media such as documents, data, photos, and videos. You may access these files from anywhere and on any device (laptop, mobile phone, tablet etc). With cloud computing, users are able to allocate their computing needs among a shared pool of powerful machines, increasing their access to resources like processing power, storage space, and software services. There is a growing population of internet users who rely on cloud-based resources. Large amounts of data are transferred from users to hosts and from hosts to users in the cloud environment, but as demand for cloud services grows, the associated cost and complexity for the cloud provider may become unsustainable. There may be times when two or more users make a request for the same item. Given these constraints, it's not easy to decide which host to use to gain access to the necessary resources and build a virtual machine (VM) in which to run the necessary applications in a way that maximises efficiency while minimising costs. Scheduling tasks in a cloud computing environment to maximise efficiency is one solution to this issue. An approach to job scheduling is provided by this project. In this research, we make an effort to suggest a host selection model based on shortest execution time to reduce overhead.